Out of Sight, Out of Mind? Evidence of Perceptual Factors in the Multiple-Category Discount - Leung, Ming D.; Sharkey, Amanda J. (Organization Science, 2014)
Extant work shows that market actors who span multiple social categories tend to be devalued relative to their more specialized peers. Scholars typically explain this pattern of results with one of two arguments. Some contend that perceptual factors—namely, the difficulties that buyers have in making sense of category spanners—contribute to the observed pattern of devaluation. Others argue that the penalty for category-spanning stems from the fact that those who do not focus their efforts narrowly tend to offer products that are of lower quality. Because these two mechanisms often co-occur, it has been difficult to provide definitive evidence of the perceptually driven component of the multiple-category penalty. We employ a natural experiment on a peer-to-peer crowd-funding website to address this gap. Difference-in-difference analyses on matched samples show that category spanning is perceived negatively and can result in devaluation, even in the absence of underlying quality differences. This result supports the argument that perceptual issues contribute to the penalty for category spanning.